Analisis Kondisi Keruntuhan Dan Beban Tekuk Kolom Profil Baja - KALANGI, Hendry Tanoto; TANIJAYA, Jonie; WITANTO, Ronald Likar (Fakultas Teknik Universitas Katolik Santo Thomas, 2019)
This study discussed the H and WF steel profiles that encountered axial compressive forces. A structural element with a straight geometry was loaded by axial compressive forces which is started from 1 N until the highest load that could be achieved. This simulations was done by finite element method program of Ansys R18.0. In this study, an analysis of the H and WF steel profiles was carried out to obtain failure conditions and the value of buckling load that can be achieved from the steel profile with variations in type of restraints. The buckling load analysis is carried out theoretically (literature) and compared with eigenvalue buckling by Ansys R18.0. The buckling load generated by Ansys R18.0 will also be analyzed to obtain the effective length conversion factor (K) and then compare it with the K value got from the existing literature.The results showed both H and WF steel profile underwent failure by flexural buckling conditions, meanwhile the largest buckling load is 1.452,5729 kN of H 200x200x12x8 profile with fixed-fixed type of restraints, and the smallest buckling load was found 1,7639 kN of WF 100x50x7x5 profile with fixed-free type of restraints by the theoretical analysis. The effective length conversion factor (K) by using Ansys R18.0 was found 6% smaller than the existing literature. The buckling loads calculated by Ansys R18.0 was found 12% greater than the results of theoretical analysis